Aggressiveness of Cuban Papaya ringspot virus Isolates on Carica papaya L. cv. Maradol Roja under Greenhouse Conditions - Cabrera Mederos, Dariel (2017)
Carica papaya is a major fruit crop in tropical and subtropical regions; however, its production has several constraints. Papaya ringspot virus (PRSV) is the most important pathogen affecting papaya plantations. Symptoms induced by a known PRSV isolate on papaya plants after mechanical inoculation were described to elaborate an evaluation scale under greenhouse conditions. The aggressiveness of 24 Cuban PRSV isolates was determined by assessing symptom severity induced on papaya plants cv. Maradol roja under greenhouse conditions. An evaluation scale of 0 to 6 scores was elaborated based on the observations of PRSV symptom progress. Symptoms induced by Cuban PRSV isolates included vein clearing, mottling and swelling zones on the adaxial leaf surface, slight deformation of young leaves and distortion. PRSV isolates from Nueva Paz, Güines, and San José de Las Lajas in the west, Sancti Spíritus in the center, and Palma Soriano and Puerto Padre in the east of the country were the most aggressive according to their area under the disease progress curve values. Knowledge about the aggressiveness of this virus is crucial for selecting PRSV isolates to implement management strategies and papaya breeding programs in Cuba.